Intravitreal Chemotherapy in the Management of Vitreous Disease in Retinoblastoma. Issue 4 (26th June 2017) - Kiratli, Hayyam; Koç, İrem; Varan, Ali; Akyüz, Canan
Purpose: To evaluate the therapeutic outcome of intravitreal melphalan injection in the management of vitreous disease in patients with retinoblastoma. We particularly aimed to assess whether higher melphalan dose with lower number of injections was more effective and associated with fewer side effects. Methods: This retrospective, interventional, noncomparative, and nonrandomized study included 39 eyes of 37 patients. Vitreous seeds were classified as dust, sphere, and cloud types. Intravitreal injections were performed through pars plana free of any visible tumor using 30-G needle. Response of the seeds (disappearance, conversion into inactive debris, or progression) and enucleation rate were determined as outcome measures. Results: All patients previously received systemic or intra-arterial chemotherapy. Vitreous seeding was primary in 54% of eyes and secondary in 46% of eyes. Vitreous seeds were classified as dust in 9 (23.1%) eyes, sphere in 24 (61.5%) eyes, and cloud in 6 (15.4%) eyes. Melphalan dose varied between 20 and 40 µg and 20 (51.3%) eyes received >30 µg. The total number of injections was 70 (range 1-5, mean 1.8 per eye). Various types of regression were obtained in 27 (69.2%) eyes. Sphere-type seeds were the most responsive to melphalan. Nonresponse and disease progression were noted in 12 (30.8%) eyes. After a mean follow-up of 11.8 months, 17 (44%) eyes were enucleated. Vitreous hemorrhage (18%) and retinal pigment epithelial alterations (8%) were the most common side effects. Conclusions: Intravitreal melphalan at 30-40 µg in 1 or 2 injections proved effective in 69.2% of eyes with vitreous disease.